The End of Animal Welfare Labelling as We Know It? Persisting Problems at the Consumer Level and PLF-Based Solutions - Ingenbleek, Paul T. M.; Krampe, Caspar (Frontiers in Animal Science, 2022)
Over the last few decades, animal welfare (AW) labels have become permanent factors in consumer markets for animal-based food products across Europe. During this time, scholarly thinking about consumer perspectives on AW labelling has identified problems that hinder the effectiveness of labels, pertaining to (i) consumers’ trust in labels, (ii) the number of labels present in the market, (iii) confusion about the meaning of labels, (iv) trade-offs between AW labels and price, (v) consistency between the AW standards and consumers’ individual opinions about AW and (vi) the ability of animal-based sectors to innovate in AW labelling. Based on these insights, this study explores the current state of these problems by questioning 2.433 consumers from four countries in the European Union (Finland, the Netherlands, Spain, and Italy) about these issues. The results show that, while opinions differ between countries and cross-border consumer segments, these issues persist for many consumers. These results cast doubt on the idea that AW labels in their traditional form can substantially increase their effect on the market. The study therefore explores potential data-based solutions to persistent consumer problems by drawing on precision livestock and e-commerce technologies. It extends current data use, which is often limited to farms and value chain actors but rarely reaches consumers. We argue that innovative technologies create opportunities to influence consumers in the often neglected pre- and post-purchase stages, through a selection system where consumers can indicate their AW preferences, receive feedback, and transparently provide insight into their preferences to other value chain actors.